Trends and patterns in pulmonary arterial hypertension-associated hospital admissions among methamphetamine users: a decade-long study - Husein, Amanda; Boullion, Jolie; Hossain, Md Ismail; Xing, Diensn; Khan, Md Tareq Ferdous; Bhuiyan, Md. Shenuarin; Kolluru, Gopi K.; Bhuiyan, Md Mostafizur Rahman; Goeders, Nicholas E.; Conrad, Steven A.; Vanchiere, John A.; Orr, A. Wayne; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background Pulmonary arterial hypertension (PAH) is a rare, chronic, progressive form of pulmonary hypertension in which increased arterial pressure causes remodeling of the arterial system and is associated with heart failure. Methamphetamine is a stimulant that has recently become a focus in PAH research, but the recent trends and demographics of this cohort of patients are not known. The study aimed to analyze the overall trends and demographics of PAH patients with and without concurrent methamphetamine usage. Methods The study used the National Inpatient Sample (NIS), Healthcare Cost and Utilization Project (HCUP), and Agency for Healthcare Research and Quality (AHRQ) from 2008 to 2020 to calculate nationally weighted estimates for both conditions by ICD-9 and ICD-10 diagnosis codes. We used several statistical measures, including descriptive statistics with design-based chi-square and t-tests, trend analysis with Cochran-Armitage test, generalized linear models, and other data preprocessing measures. Results A significant increase was evident in patients with pulmonary arterial hypertension (PAH) and concurrent methamphetamine use (9.2-fold). Most of the hospitalized patients were males (59.16%), aged 41–64 (45.77%), White (68.64%), from the West (53.09%), with Medicaid (50.48%), and with median income <25,000. The rate of increase over the period was higher for males (11.8-fold), race (not sure which race; please check and modify), aged 41–64 (11.3-fold), and in the South (15.1-fold). An overall adjusted prevalence ratio (PR) for PAH hospitalizations among concurrent methamphetamine users was 32.19 (CI = 31.19–33.22) compared to non-users. With respective reference categories, the significantly higher PR was evident for males, patients aged 41–64, White, with Medicare, median income <25,000, all regions compared to Northeast, length of hospital stays, and conditions, including chronic pulmonary disease, diabetes, hypertension, obesity, and peripheral vascular disorders. Conclusion This study reveals a national overall and demographic-specific trend of increasing PAH with concurrent methamphetamine usage and associated factors. The findings may help to understand the current patterns and identify the vulnerable sociodemographic cohorts for further research and to take appropriate policy measures.